Nurse Turnover Intention Related to Job Stress and Job Satisfaction: Literature Review - Febrina Tarawan; Sella Dwi Astia Ningrum (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: The nursing profession, which constitutes the largest professional group within the healthcare system, plays a crucial role in ensuring the quality of nursing services and patient safety. Currently, the world is facing a serious challenge in the form of a nursing shortage, with an estimated deficit of about 5.7 million professional nurses globally by 2030. Studies have shown that Southeast Asia and the Pacific have the highest nurse burnout rates, at 13.68%. 24 This job burnout indicates that nursing is one of the professions with higher levels of stress and workload because it involves patient care. The work stress resulting from excessive workload leads to nurse turnover intention. The turnover intention for nurses in their first year of work is 27.1%.27 The heavy workload drives nurses to leave, and this turnover intention contributes to the nursing shortage. Objective: This literature review aims to determine the relationship between nurse turnover intention, work stress, and job satisfaction. Method: A literature review study was conducted using databases such as Google Scholar, PubMed, ProQuest, and Scopus. Article selection followed the PRISMA protocol, including identification, screening, eligibility, and analysis of 11 articles. Result: The analysis results showed a significant relationship between work stress and job satisfaction with nurse turnover intention. Conclusion: Addressing the work stress experienced by nurses and improving job satisfaction is expected to mitigate the turnover intention among nurses.